Rising Inequality and Intergenerational Mobility: The Role of Public Investments in Human Capital - Aizer, Anna (CESifo Econ Stud, 2014)
One consequence of the rise in inequality witnessed over the past 40 years is its potentially negative impact on intergenerational mobility if parents at the bottom of the income distribution invest significantly less in their children's human capital. I consider whether public investments in children can potentially offset the inequality of private investments. Specifically, examining changes in public spending in 25 Organization for Economic Co-operation and Development countries over the period 2000–2009, I find that increases in spending on health are most strongly associated with reductions in the importance of family background and declines in inequality in the production of child human capital as measured by the Program for International Student Assessment test scores among 15-year-olds. Public spending on family support, housing, and education are also moderately related. In contrast, increased spending on the elderly is associated with increases in the importance of parental background and inequality of child test scores. These results suggest that public investments in child human capital have the potential to offset the potentially negative impact of increasing income inequality on intergenerational mobility and inequality of the next generation. Further research firmly establishing a causal relationship is needed.